Hybrid-delivered community psychoeducation for people aged 50 and older: A mixed-method evaluation and lesson learned - Dara Kiu Yi Leung; Nicole Hiu Ling Wong; Jessie Ho Yin Yau; Frankie Ho Chun Wong; Tianyin Liu; Wai-wai Kwok; Gloria Hoi Yan Wong; Terry Yat Sang Lum (Internet Interventions, 2024)
Introduction: Hybrid training mode comprising in-person and teleconferencing sessions is effective and sustainable, yet no standardized principles guide its development for older people. This study aimed to develop a set of principles for hybrid-mode psychoeducation for older people from the experiences of middle-aged and older people in two folds: (1) examining the effects of hybrid-mode community psychoeducation and (2) identifying features that could enhance participants' experience. Methods: We delivered 12-hour Older Person Mental Health First Aid and 3-hour late-life depression training to adults aged 50 and older in in-person and hybrid modes. Hybrid group participants received technology-related support, including in-advance training and on-site support. All participants completed assessments on depression literacy, depression stigma, meaning in life, social support, depressive symptoms, and anxiety pre-and post-intervention and evaluated the program in open-ended questions. Results: A total of 471 in-person and 346 hybrid group participants completed the psychoeducation and post-assessment (80.4 % female, mean age = 64.73 years, SD = 7.29). Linear mixed models revealed improvements in depression literacy, depression stigma, meaning in life, social support, and anxiety (B = −1.43 to 0.13, all p < .001), with no significant difference between in-person and hybrid groups. Thematic analysis of open-ended questions identified three themes: (1) informational content with case studies, (2) hardcopy course handouts, and (3) interactive learning environment. Discussion/conclusion: Hybrid-mode and in-person psychoeducation had comparable benefits on middle-aged and older people. The TORCH principles, an acronym for Technology provision, On-site technical support, Rehearsal, Connection with group members, and Hardcopy notes, was derived from practice wisdom and qualitative findings to support older people in online learning.